The Role of Microfinance in Driving Economic Growth and Financial Inclusion in India - C, Dhanalakshmi; B, Rohith; V M, Bhavya (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
Finance is the foundation of the economic development of a country. Financial activities contribute to the growth of a country’s economy. India has transformed the entire financial sector with the introduction of inclusive finance, digitization and other regulations and has become an excellent financial service provider. However, it is still difficult to popularize rural finance practices. Microfinance is crucial in addressing the financial requirements in backwoods communities. It is also instrumental in the emergence of Self-Help Groups (SHGs), small business owners and new entrepreneurs. Microfinance integrates the financial services system by identifying its target customers and preparing financial products according to the exigency of the unorganized sector. Presently, microfinance has grown by 21% in FY2023 (FY2023) compared to FY2022 (FY2022). This study focuses on the play of microfinance in providing adequate finance to various sectors of the unorganized sector in India and facilitating economic growth.